Más allá del ruido: Una historia del Hip Hop en Colombia (Papeles, 2010)
This article is part of the research entitled “La palabra cantada como resistencia. hip hop, Revolución en Arte Popular”, the researcher developed as a thesis to qualify for the title of Master of Interdisciplinary Social Research at the Universidad Distrital Francisco José de Caldas. The concern revolves around establishing the origins of hip hop as a movement youth identity to rebuild its history, to trace the major influences that feed sound and its first appearance in North America, thus determining the conditions under which appears in Colombia and in determining a horizon in which one can understand the hip hop from a genealogical perspective, ie as a category of analysis for the social sciences today
Keywords: Hip hop; Music; identities; subjectivities; rap; history; resistance; break dance; graffiti